English fiction in the 1930s : language, genre, history - Hopkins, Chris, 1960- (Continuum literary studies., 2006)
This study approaches the fiction of the 1930s through critical debates about genre, language and history, setting these in their original context, and discussing the generic forms most favoured by novelists at the time.